Examining birth preparedness and complication readiness: a systematic review and meta-analysis of pregnant and recently delivered women in India - Tanya Singh; Brajaraj Tripathy; Anuj Kumar Pandey; Diksha Gautam; Sidharth Sekhar Mishra (BMC Women's Health, 2024)
Abstract Background Birth preparedness and complication readiness (BPCR) is an essential component of safe motherhood programs. This study aims to systematically identify and synthesize available evidence on birth preparedness and complication readiness among pregnant and recently delivered women in India. Methods The study followed PRISMA guidelines and used databases such as PubMed, Cochrane Library, and ProQuest. Joanna Briggs Institute [JBI] Tool was used for critical appraisal of studies. The meta-analysis was conducted using Comprehensive Meta-Analysis [CMA] tool and R studio software. Statistical heterogeneity was evaluated using visual inspection of the forest plot, Cochran’s Q test, and the I2 statistic results. Funnel plot and Egger’s tests were applied to explore the possibility of the publication bias in the studies [PROSPERO: CRD42023396109]. Result Thirty-five cross-sectional studies reported knowledge on one or more components of birth preparedness [BP], whilst knowledge on complication readiness [CR] or danger signs was reported in 34 included studies. Utilizing the random effect model, the pooled result showed that only about half of the women [49%; 95% CI: 44%, 53%] were aware on BPCR components. This result ranged between 15% [95% CI: 12%, 19%] to 79% [95% CI: 72%, 84%] in Maharashtra and Karnataka respectively [I2 = 94%, p = < 0.01]. High heterogeneity [> 90%] is observed across all components [p < 0.01]. The result of subgroup analysis indicated no significant difference in the proportion on BPCR among pregnant women [50%; 95% CI: 45%, 55%] and recently delivered women [54%; 95% CI: 46%, 62%]. However, the southern region of India indicates relatively better [56%; 95% CI: 45%, 67%] prevalence. Conclusion Our study highlights the low prevalence of BPCR in India and the factors associated with it. Scaling up cost-effective interventions like BPCR that have a positive overall effect is necessary. Authors strongly suggests that birth preparedness and complication readiness should be given utmost importance to reduce maternal morbidity and mortality to achieve the Sustainable Development Goals. Consideration should be given to fortifying existing resources, such as frontline workers and primary healthcare, as a strategic approach to augmenting the effectiveness of awareness initiatives.